Didactic Digital Material for the Teaching of English to Second Grade Children (2020)
The main objective of this work is to develop a digital teaching resource for teaching English to second-grade children of the Liceo Patria School, Bucaramanga; in order to achieve this objective, the researchers took into account the preferences and needs of students. The proposed resource; a digital fable's book was designed for this research with the aim of improving the speaking and listening skills in students. Aiming for the effectiveness of the teaching material, this research also integrates the use of CLIL methodology. This methodology seeks to integrate both the learning of contents and the learning of languages. Using the CLIL approach, students learn one or more subjects, learn about a topic, and at the same time learn a second language. Using this approach in class students can achieve the development of the skills for their learning (learning skills). In addition, the design of the material is presented, in which it seeks to develop in the student speaking and listening skills, for this reason, all the activities revolve around the implementation of these skills in an individual and group way, seeking equally encourage cooperative work among students. Due to time constraints, this research project was designed and developed to a certain extent. The research proposes a pedagogical intervention along with the designed material but was not implemented at the school. Keywords: skills, teaching-learning, education, didactic materials, thematic unit, digital book, English language.